Uncertainty in an Interconnected Financial System, Contagion, and Market Freezes - Mei Li; Frank Milne; Junfeng Qui (Queen's University, Department of Economics, 2013)
This paper studies contagion and market freezes caused by uncertainty in financial network structures and provides theoretical guidance for central banks. We establish a formal model to demonstrate that, in a financial system where financial institutions are interconnected, a negative shock to an individual financial institution could spread to other institutions, causing market freezes because of creditors' uncertainty about the financial network structure. Central bank policies to alleviate market freezes and contagion, such as information policy, bailout policy and the lender of last resort policy, are examined.
Keywords: D82; G2; 330; Interconnection; Market Freezes; Contagion; Financial Crises